2018
DOI: 10.1155/2018/8037965
|View full text |Cite
|
Sign up to set email alerts
|

Public Awareness on Cord Blood Banking in Saudi Arabia

Abstract: Background In the last decade, cord blood (CB) has proven to be a valuable source of hematopoietic stem cells for transplantation to treat many hematological disorders. Since then, many CB banks have been established worldwide. Our aim was to estimate the level of public awareness of CB banking in Saudi Arabia. Study Design and Methods A self-administered questionnaire of 22 multiple choices was conveniently distributed, consisting of demographics, awareness measure, attitude toward banking preference, and don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 15 publications
(10 reference statements)
2
20
0
Order By: Relevance
“…Similar to the study by Dinc and Sahin [16] which examined knowledge of Turkish participants about cord blood banking, found that around 70% had poor or very poor knowledge, which was similar to the findings reported by of Fernandez et al [17]. This lack of knowledge is consistent with other studies, such as the one conducted by Jawdat et al [18], in which more than half of the Saudi Arabian respondents were unaware of CB banking, and the study by Matsumto et al [19] showing that 75% of women participants knew nothing about CB banking in Jordan. However, better awareness was indicated in Australian pregnant women, where 70% of the respondents had adequate knowledge about CB banking [20,21].…”
Section: Discussionsupporting
confidence: 91%
“…Similar to the study by Dinc and Sahin [16] which examined knowledge of Turkish participants about cord blood banking, found that around 70% had poor or very poor knowledge, which was similar to the findings reported by of Fernandez et al [17]. This lack of knowledge is consistent with other studies, such as the one conducted by Jawdat et al [18], in which more than half of the Saudi Arabian respondents were unaware of CB banking, and the study by Matsumto et al [19] showing that 75% of women participants knew nothing about CB banking in Jordan. However, better awareness was indicated in Australian pregnant women, where 70% of the respondents had adequate knowledge about CB banking [20,21].…”
Section: Discussionsupporting
confidence: 91%
“…Alhadlaq et al in their study regarding implications of stem cells in dentistry observed poor knowledge among the male and females students ( Alhadlaq et al., 2019 ). Jawdat et al. (2018) in their study in general population observed poor knowledge about Cord Blood banking with 66% of participants possessing inadequate knowledge.…”
Section: Discussionmentioning
confidence: 88%
“…Throughout the World, public cord blood banks (CBBs) store more than 700,000 UCB units. There are 2 public CBBs in Saudi Arabia but no private CCBs are present ( Jawdat et al., 2018 ). Most studies have shown inadequate knowledge and awareness among public and healthcare staff about CB banking ( Perlow, 2006 ; Suen & Lao, 2011 ; Tuteja, Agarwal & Phadke, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Poland, that phenomenon can be connected with advertising and a strong private network of cord blood banks, which store cord blood for future use by the donor or his/her relatives. However, many studies have also demonstrated a positive attitude towards cord blood donation, even towards public storage [ 30 , 31 ]. The results obtained show that some pregnant women knew that additional perinatal tissues containing stem cells with potential therapeutic value are routinely discarded as medical waste.…”
Section: Discussionmentioning
confidence: 99%